An outline of American history (New York, 1994)
An Outline of American History is one of the oldest continuing publications od the United States information Agency. The first edition (1949 - 50) was produced under the sditorship of Francis Whitney, frist of the State Department Office of International Information and later of the U. S. Information Agency.
Keywords: America,America; Description and travel,History